THE EFFECT OF GENDER DIVERSITY, POLITICAL CONNECTION, CAPITAL INTENSITY, AND INVENTORY INTENSITY ON TAX AVOIDANCE IN STATE-OWNED ENTERPRISES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020–2023 - Olivia Larassati; Sarwenda Biduri (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: The purpose of this study is to examine the Influence of Gender Diversity, Political Connection, Capital Intensity and Inventory Intensity on Tax Avoidance. Method: In this study, the population data used are all BUMN Go-Public Companies. The companies that are the samples of this study were selected using the purposive sampling method, where the sample is selected based on certain considerations or certain characteristics. There are 23 companies that are used as samples with 4 periods so that the data to be processed is 92 data. The data analysis technique used is multiple linear regression with SPSS version 27 data processing tools. Results: The results of this study can be concluded that Gender Diversity has a positive effect on Tax Avoidance. Political Connection has a positive effect on Tax Avoidance. Capital Intensity has a positive effect on Tax Avoidance. Inventory Intensity has a positive effect on Tax Avoidance. Novelty: This study provides empirical evidence on the simultaneous influence of Gender Diversity, Political Connection, Capital Intensity, and Inventory Intensity on Tax Avoidance in BUMN Go-Public Companies, offering insights into how company characteristics and governance factors contribute to tax avoidance behavior.